PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN UNO BOARD GAME CAFE MALANG - Gerardea, Francisca Alfarah; Suryadi, Nanang (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study was conductedtoexaminethe influence ofexperiential marketingto customer satisfactionUNOBoard GameCafeMalang. This research isexplanatory researchthroughquestionnairemethod. The samplein this studywas90respondents whoare consumersofUNOBoard GameCafe. The results ofobservationswere analyzedusingmultiple linearregressionanalysistestandhypothesis testing. Hypothesis Testingisusedto simultaneouslytesthypothesesandpartial hypothesis. Regression analysis showed that Experiential Marketing variables(sense(X1), feel(X2), think(X3), act(X4) andrelate(X5))have a simultaneous affectthe dependent variableof customer satisfaction(Y). Partial test resultsthat showsignificant resultsis thesensevariable(X1), think(X3), andrelate(X5). Keywords: Experiential Marketing,Sense, Feel, Think, Act, Relate, Customer Satisfaction